Efecto del tratamiento sobre el descuento temporal y probabilístico en participantes con trastorno por uso de crack - Diana Mejía; Silvia Morales-Chainé; Javier Nieto (Centros de Integración Juvenil A.C., 2016)
Introduction: several studies have shown that individuals with dependence on psychoactive drugs show a steeply delay discounting with monetary rewards in contrast to non-consumers. This finding is clinically useful as a behavioral trait likely to be modified by psychological treatments. Objective: this study evaluated changes pre-post measures of delay and probability discounting, somatic symptoms, anxiety, depression, psychosis and self-efficacy in participants with crack use disorder severe who received one of two types of psychological treatment. Method: we worked with ninety two participants, 31 for each treatment and 30 in the control group. We evaluated the three groups so pre-post, the post was held after 40 days for the three groups, and during that time the cocaine users received one of the two forms of treatments, except control who only received post evaluation. Results: the results showed that the pre-post evaluation with probability and delay discounting procedures did not change in any of the three groups. Suggesting that the discounting is not sensitive to identify short-term changes as result from psychological interventions. In contrast both treatment modalities increased self-efficacy, and reduced symptoms of somatization, anxiety, depression and psychosis. Not a main effect for treatment type was found. Discussion and conclusions: this study showed the stability of discounting measures with psychological treatment. While other variables they were subject to change due to the treatment, so the clinical utility of the discounting as a variable indicating the success of the intervention should be further explored in future research.----------------------- Introducción: diversos estudios han mostrado que individuos con dependencia de drogas psicoactivas muestran un descuento temporal pronunciado de recompensas monetarias en contraste con no consumidores. Este hallazgo resulta de utilidad clínica como una característica conductual susceptible a modificación por tratamientos psicológicos. Objetivo: evaluar modificaciones pre-post en descuento temporal y probabilístico, sintomatología somática, ansiedad, depresión, psicosis y autoeficacia, en participantes con trastorno por uso de crack severo que recibieron una de dos modalidades de tratamiento psicológico y en un grupo control sin consumo. Método: se trabajó con 92 participantes, 31 en cada uno de los tratamientos y 30 en el grupo control. Se evaluó a los tres grupos de manera pre-post; el post se llevó a cabo después de 40 días para los tres grupos, tiempo durante el cual recibían alguna de las dos modalidades de atención, a excepción del grupo control, al cual se le dio cita para la evaluación post. Resultados: las mediciones pre-post de descuento temporal y probabilístico no cambiaron en ninguno de los tres grupos. En contraste, ambas modalidades de tratamiento incrementaron la autoeficacia y disminuyeron síntomas somáticos como ansiedad, depresión y psicoticismo. Discusión y conclusiones: se demostró la estabilidad de las mediciones de descuento ante el tratamiento psicológico; otras variables sí fueron susceptibles de modificación debido al tratamiento, por lo que la utilidad clínica del descuento, como una variable que indique el éxito de la intervención, debe seguir explorándose en futuras investigaciones.